AI-BASED GAMIFICATION IN LEARNING: AN ANALYSIS OF ITS IMPACT ON STUDENTS’ ENGAGEMENT - A MIXED METHODS STUDY - Jiny Dharma Ditha; Susanto Susanto; Taridi Taridi; Ayu Ardiyaningsih (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
Declining student engagement is a crucial challenge in the global education system in the era of digital transformation, demanding innovative interventions such as the integration of artificial intelligence (AI) technology. This study aims to evaluate the impact of implementing AI-based gamification on student learning engagement, given the urgent need for adaptive learning strategies for the digital generation. Using a mixed-methods research design with a sequential explanatory strategy, this study collected data through a quantitative survey of 43 students and qualitative in-depth interviews. Statistical analysis revealed a significant positive correlation (r=0.560), with regression analysis confirming that gamification elements contributed 31.3% to increased student participation. Qualitative findings support this result by demonstrating that features such as points, badges, automated feedback, and content personalization are effective in stimulating intrinsic motivation and learning consistency, although competitive elements such as leaderboards need to be managed judiciously to avoid excessive pressure. Overall, the study concludes that AI-based gamification is an effective strategy for fostering student cognitive and emotional engagement and recommends the development of a varied and adaptive reward system to maintain long-term learning motivation. ABSTRAK Penurunan keterlibatan siswa menjadi tantangan krusial dalam sistem pendidikan global di era transformasi digital, yang menuntut adanya intervensi inovatif seperti integrasi teknologi kecerdasan buatan (AI). Penelitian ini bertujuan untuk mengevaluasi dampak penerapan gamifikasi berbasis AI terhadap keterlibatan belajar siswa, mengingat urgensi kebutuhan strategi pembelajaran yang adaptif bagi generasi digital. Menggunakan desain penelitian metode campuran (mixed-methods) dengan strategi eksplanatori sekuensial, studi ini mengumpulkan data melalui survei kuantitatif terhadap 43 mahasiswa dan pendalaman kualitatif melalui wawancara. Analisis statistik menunjukkan adanya korelasi positif yang signifikan (r=0,560), di mana analisis regresi mengonfirmasi bahwa elemen gamifikasi berkontribusi sebesar 31,3% terhadap peningkatan partisipasi siswa. Temuan kualitatif memperkuat hasil ini dengan menunjukkan bahwa fitur seperti poin, lencana, umpan balik otomatis, dan personalisasi konten efektif dalam memicu motivasi intrinsik dan konsistensi belajar, meskipun elemen kompetitif seperti leaderboard perlu dikelola dengan bijak agar tidak menimbulkan tekanan berlebih. Secara keseluruhan, penelitian menyimpulkan bahwa gamifikasi berbasis AI merupakan strategi efektif untuk menumbuhkan keterlibatan kognitif dan emosional siswa, serta merekomendasikan pengembangan sistem penghargaan yang variatif dan adaptif guna menjaga motivasi belajar jangka panjang.